2014
DOI: 10.1186/2045-824x-6-5
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages in solid organ transplantation

Abstract: Macrophages are highly plastic hematopoietic cells with diversified functions related to their anatomic location and differentiation states. A number of recent studies have examined the role of macrophages in solid organ transplantation. These studies show that macrophages can induce allograft injury but, conversely, can also promote tissue repair in ischemia-reperfusion injury and acute rejection. Therapeutic strategies that target macrophages to improve outcomes in solid organ transplant recipients are being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 115 publications
(137 reference statements)
1
20
0
2
Order By: Relevance
“…Following transplantation, the graft microvasculature encounters multiple insults including ischemia reperfusion injury and alloimmune attack (8, 32). Despite treatment with powerful immunosuppressants, the graft microvascular circulation sustains repetitive injury followed by inadequate regeneration which eventually leads to prolonged tissue hypoxia and accelerated fibrotic remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Following transplantation, the graft microvasculature encounters multiple insults including ischemia reperfusion injury and alloimmune attack (8, 32). Despite treatment with powerful immunosuppressants, the graft microvascular circulation sustains repetitive injury followed by inadequate regeneration which eventually leads to prolonged tissue hypoxia and accelerated fibrotic remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Activated T cells also recruit a large number of innate cells including macrophages and granulocytes into the allograft where they either directly or indirectly mediate graft failure. Following transplantation, macrophages can also differentiate into many functionally different subsets, mediating phagocytosis of necrotic cells, secretion of pro-inflammatory cytokines, production of reactive oxygen species, as well as mediating tissue repair, regeneration, and immunoregulation [5]. Other innate cells involved in allograft rejection include natural killer (NK) cells.…”
Section: Introductionmentioning
confidence: 99%
“…Independently of allograft type, macrophages accumulation and activation occur within the early phase of IRI processes triggering quick and intense innate immune response activation and organ injury (42). Moreover, through the production of pro-inflammatory mediator and its capacity as antigen presenting cells, accumulated macrophages may promote adaptive T cell response (18,42).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, through the production of pro-inflammatory mediator and its capacity as antigen presenting cells, accumulated macrophages may promote adaptive T cell response (18,42). Previous studies demonstrated increased activity of Kupffer cells (KC), the hepatic macrophage, in steatotic liver allografts (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation